Routine postoperative antibiotic prophylaxis offers no benefit after hepatectomy: a systematic review and meta-analysis - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Teroerde, Miriam; Chiriac, Ute; Klotz, Rosa; Hornuß, Daniel; Larmann, Jan; Weigand, Markus A.; Hoffmann, Katrin (Antibiotics, 2022)
Background: Prophylactic antibiotics are frequently administered after major abdominal surgery including hepatectomies aiming to prevent infective complications. Yet, excessive use of antibiotics increases resistance in bacteria. The aim of this systematic review and meta-analysis is to assess the efficacy of prophylactic antibiotics after hepatectomy (postoperative antibiotic prophylaxis, POA). Method: This systematic review and meta-analysis were completed according to the current PRISMA guidelines. The protocol has been registered prior to data extraction (PROSPERO registration Nr: CRD42021288510). MEDLINE, Web of Science and CENTRAL were searched for clinical reports on POA in hepatectomy restrictions. A random-effects model was used for synthesis. Methodological quality was assessed with RoB2 and ROBINS-I. GRADE was used for the quality of evidence assessment. Results: Nine comparative studies comprising 2987 patients were identified: six randomized controlled trials (RCTs) and three retrospectives. POA did not lead to a reduction in postoperative infective complications or have an effect on liver-specific complications—post-hepatectomy liver failure and biliary leaks. POA over four or more days was associated with increased rates of deep surgical site infections compared to short-term administration for up to two days (OR 1.54; 95% CI [1.17;2.03]; p = 0.03). Routine POA led to significantly higher MRSA incidence as a pathogen (p = 0.0073). Overall, the risk of bias in the studies was low and the quality of evidence moderate. Conclusion: Routine POA cannot be recommended after hepatectomy since it does not reduce postoperative infection or liver-specific complications but contributes to resistance in bacteria. Studies into individualized risk-adapted antibiotic prophylaxis strategies are needed to further optimize perioperative treatment in liver surgery.